2020
DOI: 10.1080/03007995.2020.1799772
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization and costs associated with postpartum depression among commercially insured households

Abstract: Objective: To quantify the economic burden of postpartum depression (PPD) that accrues to commercially insured households in the year following childbirth. Methods: Administrative claims data from OptumHealth Care Solutions (2009-2016) were used to identify households that included women identified with PPD per the algorithm and propensity score-matched comparison households of women who were not identified with PPD or a history of depression after childbirth. Study outcomes included direct total all-cause med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…They self‐reported that the use of donor human milk reduced symptoms of postpartum depression and anxiety and provided psychological comfort that formula could not 42 . This indicates a possibility of further savings in health care cost given that medical and pharmaceutical spending incurred households with women diagnosed with postpartum depression is 22% higher than those with women without depression 43 . Considering that this was a small‐scale study and the benefit was limited to donor human milk recipients, more evidence is needed to verify the cost‐saving potential through larger scale quantitative and comparison studies.…”
Section: Cost‐effectiveness Of Donor Human Milk Usementioning
confidence: 99%
See 1 more Smart Citation
“…They self‐reported that the use of donor human milk reduced symptoms of postpartum depression and anxiety and provided psychological comfort that formula could not 42 . This indicates a possibility of further savings in health care cost given that medical and pharmaceutical spending incurred households with women diagnosed with postpartum depression is 22% higher than those with women without depression 43 . Considering that this was a small‐scale study and the benefit was limited to donor human milk recipients, more evidence is needed to verify the cost‐saving potential through larger scale quantitative and comparison studies.…”
Section: Cost‐effectiveness Of Donor Human Milk Usementioning
confidence: 99%
“…42 This indicates a possibility of further savings in health care cost given that medical and pharmaceutical spending incurred households with women diagnosed with postpartum depression is 22% higher than those with women without depression. 43 Considering that this was a small-scale study and the benefit was limited to donor human milk recipients, more evidence is needed to verify the cost-saving potential through larger scale quantitative and comparison studies. Nevertheless, the use of donor human milk may salvage breastfeeding relationships that eventually lead to motivation to continue lactation efforts.…”
Section: Cost-effectiveness Of Donor Human Milk Usementioning
confidence: 99%
“…Using parameters from the model, the RID was low (maximum value, 1.3%), suggesting a low risk to breastfed infants. PPD is associated with multiple negative consequences for mothers and children [8,[33][34][35], and standard-of-care antidepressants are among the most frequently prescribed medications during the postpartum period [26]. Previous reports have shown that patients with severe PPD who received brexanolone infusion showed a significant and rapid reduction in their 17-item Hamilton Rating Scale for Depression total score compared with placebo, with a durable response [14,15,21].…”
Section: Discussionmentioning
confidence: 99%
“…The model included monthly health care costs for individuals and their children, which were higher when the individual was depressed, based on costs reported in the cost-effectiveness study that provided the conceptual foundation for the present model and other literature specific to the Medicaid population. 16 , 34 , 35 , 36 , 37 , 38 , 39 While PPD also causes spillovers into increased health care costs for other household members, including partners and other children, we did not include those costs here, nor productivity benefits. We calculated intervention costs when provided as individual counseling (mean [SD], $761.94 [$225.66] per person), group-based counseling (mean [SD], $137.74 [$40.80] per person), and the additional costs of antenatal screening ($2.27) when relevant, based on the Medicaid fee schedule from a representative state and based on a distribution of expected sessions attended, drawn from the meta-analysis of the preventive interventions.…”
Section: Methodsmentioning
confidence: 99%